Vision screening in children: a retrospective study of social and demographic factors with regards to visual outcomes. Issue 8 (23rd November 2015) - O'Colmain, U; Low, L; Gilmour, C; MacEwen, C J
Abstract : Background: Amblyopia and its risk factors have been demonstrated to be more common among children from low socioeconomic backgrounds. We sought to investigate this association in a region with orthoptic-delivered screening and whole population coverage, and to also examine the association of the Health Plan Indicator (HPI) with screening outcome. Methods: Screening examination outcomes, postcodes and HPIs were extracted from the community child health database for every child who underwent preschool vision screening between March 2010 and February 2011 Tayside. We obtained the Scottish Index of Multiple Deprivation score for every child as a measure of area-based deprivation. We assessed the vulnerability/needs of the individual family through the HPI—'Core' (children and families receiving universal health visiting service), 'Additional' (receiving additional health/social support) and 'Intensive' (receiving high levels of support). The outcomes from follow-up examinations for those who failed screening were extracted from the orthoptic department database. Results: 4365 children were screened during the year 2010–2011 of whom 523 (11.9%) failed. The odds of children from the least deprived socioeconomic group passing the visual screening test was 1.4 times higher than those from the most deprived socioeconomic group (OR 1.4, 95% CI 1.07 to 1.89, p=0.01). The odds of a child from a family assigned as 'Intensive' failing the preschool visual screening test was three times greater than the odds of a child from a family assigned as 'Core' (OR 3.59, 95% CI 1.6 to 7.8, p=0.001). Conclusions: We found that children from the most deprived backgrounds and those from unstable homes were more likely to fail preschool vision screening.